Comparison of digital watermarking techniques - Aparna, J. R.; Ayyappan, Sonal (International Conference for Convergence for Technology-2014, 2014)
Digital watermarking is the method of hiding digital data in any form of multimedia data such as image, audio, video, etc. Digital watermarks are used for verifying the integrity and authenticity of multimedia data and also used to prevent fraud and forgery. This paper performs a comparative analysis of different image watermarking techniques. The watermarking techniques based on DCT, DWT and a combination of DCT and DWT is implemented. These methods use Singular Value Decomposition (SVD) of the cover image and watermark for embedding the watermark. Different attacks are applied on the watermarked image in order to analyze the robustness of each algorithm.